2018
DOI: 10.1136/bmj.k4147
|View full text |Cite
|
Sign up to set email alerts
|

Making doctors better

Abstract: Personal resilience was never enough—systems must change

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Everything that Gerada and colleagues say about doctors’ wellbeing is correct 1. But despite reading very similar observations in articles, editorials, and letters, not just in The BMJ but in other medical and non-medical publications and other media over the past year, nothing has changed.…”
mentioning
confidence: 99%
“…Everything that Gerada and colleagues say about doctors’ wellbeing is correct 1. But despite reading very similar observations in articles, editorials, and letters, not just in The BMJ but in other medical and non-medical publications and other media over the past year, nothing has changed.…”
mentioning
confidence: 99%
“…18,19 Future courses and training initiatives could focus more specifically on these topics, perhaps including self-care or personal management strategies within group discussions creating a 'dedicated place for meeting, thinking and exchanging'. 20 The strengths of this project included the multiprofessional design and successful delivery of three standardised courses facilitated by similar faculty members in addition to the mixed methods approach to evaluation. Thematic analysis showed that the initially stated aims and outcomes for the course were met, and delegates achieved their personal aims and learning needs.…”
mentioning
confidence: 99%
“…Although resilience is undoubtedly needed among healthcare professionals, this is only one piece of the puzzle 1. It puts the onus on the individual, implying that lack of resilience is further evidence that doctors are failing, when they are probably already at a low ebb.…”
mentioning
confidence: 99%